AR phosphorylation and CHK2 kinase activity regulates IR-stabilized AR–CHK2 interaction and prostate cancer survival - Ta, Huy Q; Dworak, Natalia; Ivey, Melissa L; Roller, Devin G; Gioeli, Daniel (eLife, 2020)
We have previously demonstrated that checkpoint kinase 2 (CHK2) is a critical negative regulator of androgen receptor (AR) transcriptional activity, prostate cancer (PCa) cell growth, and androgen sensitivity. We have now uncovered that the AR directly interacts with CHK2 and ionizing radiation (IR) increases this interaction. This IR-induced increase in AR–CHK2 interactions requires AR phosphorylation and CHK2 kinase activity. PCa associated CHK2 mutants with impaired kinase activity reduced IR-induced AR–CHK2 interactions. The destabilization of AR – CHK2 interactions induced by CHK2 variants impairs CHK2 negative regulation of cell growth. CHK2 depletion increases transcription of DNAPK and RAD54, increases clonogenic survival, and increases resolution of DNA double strand breaks. The data support a model where CHK2 sequesters the AR through direct binding decreasing AR transcription and suppressing PCa cell growth. CHK2 mutation or loss of expression thereby leads to increased AR transcriptional activity and survival in response to DNA damage.
Keywords: prostate; CHK2; AR; androgen receptor; prostate cancer; signaling